Lymphatic Malformation Responsive to Sirolimus in Keratinocytic Epidermal Nevus Syndrome with KRAS Mutation: A Case and Brief Literature Discussion - Emily Sideris; Er Tsing Vivian Tng; Paul Chee (Karger Publishers, 2021)
We present a rare case of KRAS keratinocytic epidermal nevus syndrome with lymphatic malformation, responsive to treatment with sirolimus, an mTOR inhibitor. A brief review of the current literature regarding sirolimus use in vascular malformations, lymphatic malformations, regional overgrowth syndromes, and RASopathies is discussed.